Glycosaminoglycan Characterization by Electrospray Ionization Mass Spectrometry Including Fourier Transform Mass Spectrometry - Laremore, Tatiana N. (2010)
Electrospray ionization mass spectrometry (ESI MS) is a versatile analytical technique in glycomics of glycosaminoglycans (GAGs). Combined with enzymology, ESI MS is used for assessing changes in disaccharide composition of GAGs biosynthesized under different environmental or physiological conditions. ESI coupled with high-resolution mass analyzers such as a Fourier transform mass spectrometer (FTMS) permits accurate mass measurement of large oligosaccharides and intact GAGs as well as structural characterization of GAG oligosaccharides using information-rich fragmentation methods such as electron detachment dissociation. The first part of this chapter describes methods for disaccharide compositional profiling using ESI MS and the second part is dedicated to FTMS and tandem MS methods of GAG compositional and structural analysis.